Thermography and ultrasonography in back pain diagnosis of equine athletes - Fonseca, B. P. A.; Alves, Ana Liz Garcia [UNESP]; Nicoletti, J. L. M.; Thornassian, A.; Hussni, Carlos Alberto [UNESP]; Mikail, S. (Elsevier B.V., 2006)
The object of the current study was to evaluate the efficacy of thermography and ultrasonography in the diagnosis of thoracolumbar lesions in Quarter Horse athletes and associate the different types of lesions found with the athletic modality practiced. Twenty-four horses were admitted to the Surgery Service for Large Animals of the Veterinary and Animal Science Faculty, UNESP, Botucatu, Brazil, with complaints of back problems. All the horses were submitted for physical examinations to confirm the existence of thoracolumbar alterations and then for thermography and ultrasonography Thermography was used to map the lesioned areas of this region and ultrasonography for lesion characterization. The lesions found were supraspinous desmitis, interspinous desmitis, dorsal intervertebral osteoarthritis, and impingement of the spinous processes or kissing spines. The existence of a relation between the type of event practiced by the horse and the type of lesion found was determined. In horses that competed in the barrel race, a predominance of lesions in the thoracic caudal, thoracolumbar, and cranial lumbar regions occurred, with intervertebral osteoarthritis and interspinous desmitis being the most common. In cutting horses, most of the lesions were observed in the caudal lumbar region, whereas horses competing in reining showed a preferential location for lesions in the middle lumbar, with a predominance of supraspinous desmitis and myositis. Thermography associated with ultrasonography was shown to be efficient in the diagnosis of the thoracolumbar lesions of these horses.
Keywords: back pain; lameness; loss of performance; vertebral column